Phase III randomized trial comparing systemic versus intra-arterial oxaliplatin, combined with LV5FU2 +/- irinotecan and a targeted therapy, in the first-line treatment of metastatic colorectal cancer restricted to the liver (OSCAR): PRODIGE 49. Issue 3 (March 2022) - Pernot, Simon; Pellerin, Olivier; Mineur, Laurent; Monterymard, Carole; Smith, Denis; Lapuyade, Bruno; Gallois, Claire; Khemissa Akouz, Faiza; De Baere, Thierry; Tougeron, David; Thirot-Bidault, Anne; Audemar, Franck; et al.
Abstract: Introduction: In patients with unresectable liver metastases from colorectal cancer (CRCLM), systemic doublet or triplet chemotherapy and targeted therapy is considered a standard first-line treatment. Hepatic arterial infusion of oxaliplatin (HAI-ox) generates a high response rate, but this still needs to be confirmed in a randomized trial. We incorporated HAI-ox in doublet or triplet + targeted therapy to validate its efficacy. Aim: The OSCAR study is an ongoing randomized phase III trial comparing FOLFOX + targeted therapy according to RAS status, or FOLFOXIRI + bevacizumab in patients eligible for triplet therapy, with the same regimen but with HAI-ox instead of IV-ox as the first-line treatment for CRCLM. Materials and methods: Main eligibility criteria are colorectal cancer, unresectable liver metastasis, no extra-hepatic metastases except pulmonary nodules if ≤3 and <10 mm, ECOG performance status 0 or 1. Endpoint: The primary endpoint is progression-free survival (PFS). A difference of 4 months for the median PFS in favor of HAI-ox is expected (HR = 0.73). Secondary endpoints include overall survival, overall response rate, secondary liver resection, safety, and quality of life. Conclusion: This study is planned to include 348 patients to demonstrate the superiority of HAI-ox over systemic oxaliplatin in first-line CRCLM treatment (NCT02885753).